The changes of Treg and Th17 cells relate to serum 25(OH)D in patients with initial-onset childhood systemic lupus erythematosus - Li-jun Jiang; Zan-hua Rong; Hui-feng Zhang (Frontiers Media S.A., 2023)
BackgroundT helper 17 (Th17) cells and regulatory T cells (Treg) are known to play a crucial role in the pathogenesis of systemic lupus erythematosus (SLE). Improving the balance between Treg and Th17 cells can be a promising new therapeutic target in SLE patients. Vitamin D has a significant impact on the immune inflammatory process and the immune cells involved in this process. The purpose of this study is to investigate the relationship between Th17, Treg, cytokines, and serum 25 hydroxyvitamin D [25(OH)D] in patients with initial-onset childhood SLE.MethodsA total of 82 children aged <18 years with initial-onset SLE were included, as well as 60 healthy subjects during the same period at the Pediatrics Department of the Second Hospital of Hebei Medical University. The chemiluminescence method was performed to detect serum 25(OH)D levels. Flow cytometry was used to evaluate Treg and Th17 cells. An enzyme-linked immunosorbent assay kit was used to evaluate plasma interleukin (IL)-23, IL-17, IL-10, IL-6, and tumor necrosis factor alpha (TNF-α) concentrations.ResultThe serum 25(OH)D levels in patients with initial-onset childhood SLE were significantly lower than those in the healthy controls. The proportion of lupus nephritis (LN) was higher in the vitamin D insufficiency group (71.4%) compared with the vitamin D sufficiency group (30.3%) (p < 0.05). The SLE disease activity index (SLEDAI) was higher in the vitamin D insufficiency group (median = 14) than that in the vitamin D sufficiency group (median = 9) (p < 0.05).The 25(OH)D level was positively correlated with the Treg ratio (r = 0.337, p = 0.002), and it was negatively correlated with the Th17 cell ratio (r = −0.370, p = 0.001). The serum 25(OH)D level had a negative correlation with IL-23 (r = −0.589, p < 0.001), IL-17(r = −0.351, p = 0.001), TNF-α (r = −0.283, p = 0.01), IL-6 (r = −0.392, p < 0.001), and IL-10 (r = −0.313, p = 0.004) levels.ConclusionThe serum 25(OH)D levels decreased in patients with initial-onset childhood SLE. There was a negative correlation between the serum 25(OH)D levels and SLEDAI. The serum 25(OH)D levels in patients with initial-onset childhood SLE were negatively correlated with the Th17 ratio and related cytokines, while positively correlated with the Treg ratio.